Ecological Ethics Education Based on Outdoor Physical Activities for Students and Communities Around Campus - Rindawan, Rindawan; Mujriah, Mujriah; Sanrijaya, Niqsanding; Zainuddin, Fadli; Muhsan, Muhsan; Irmansyah, Johan (Abdi Masyarakat, 2025)
This community service project aims to raise ecological awareness among students of physical education and surrounding campus communities through educational initiatives rooted in outdoor physical activities and ecological ethics. The main problem faced by the target group is the lack of environmental awareness and sustainable behavior in daily life. The method employed combines training sessions, ecological physical activity simulations, and reflective group discussions based on real-world environmental cases. Data were collected through questionnaires, behavioral observations, and in-depth interviews. Indicators of success include improved understanding of ecological ethics, active participation, and behavioral changes in waste management and environmental preservation practices. The results demonstrate that activities such as nature trekking, eco-literacy exercises, and tree-planting projects significantly improved participants’ awareness and behavior towards environmental care. Data analysis revealed a strong positive correlation between experiential-based learning and the internalization of ecological values. These findings support previous studies highlighting the importance of hands-on learning in environmental education. The program contributes directly to the achievement of Sustainable Development Goals (SDGs), particularly Goal 13 (Climate Action) and Goal 15 (Life on Land). Furthermore, this initiative has succeeded in building a replicable model of community-based ecological education for higher education institutions.